Concentrations and trophic magnification of polychlorinated naphthalenes (PCNs) in marine fish from the Bohai coastal area, China. (March 2018) - Cui, Lili; Wang, Shasha; Gao, Lirong; Huang, Huiting; Xia, Dan; Qiao, Lin; Liu, Wenbin
Abstract: Polychlorinated naphthalenes (PCNs) have been found widely in the aquatic environment and can be transferred through food chains, which can magnify or dilute their toxic effects on humans. In this study, PCNs were analyzed in samples of 17 species of fish with different dietary habits collected in the Bohai coastal area in China. Dichloronaphthalenes, which have rarely been quantified in previous studies, were determined. The total PCN concentrations were from 7.3 to 214 pg/g wet weight, and the highest concentration was found in ditrema. The trichloronaphthalenes were the most abundant PCNs, followed by the dichloronaphthalenes and pentachloronaphthalenes. The relatively high contributions of the less-chlorinated homologs to the total PCN concentrations indicated that the main PCN sources around the Bohai were industrial thermal process emissions rather than technical PCN formulations. The trophic magnification factors of the PCN homologs were from 3.1 to 9.9, indicating that PCNs were biomagnified by fish. The trophic magnification factor of dichloronaphthalene and trichloronaphthalenes was 5.8 and 6.4, respectively, indicating for the first time that dichloronaphthalene and trichloronaphthalenes can undergo trophic magnification by fish. The two highest trophic magnification factors were for the pentachloronaphthalenes and hexachloronaphthalenes, probably because these PCNs having fewer vicinal carbon atoms without chlorine atoms attached are less easily biotransformed than the other homologs. The dioxin-like toxicities of the PCNs in the samples, expressed as potential toxic equivalences (TEQs), were assessed. The highest total TEQ was 0.0090 pg/g ww, in Pacific herring, and the hexachloronaphthalenes were the dominant contributors to the total TEQs in the fish samples. The PCN TEQs were much lower than the polychlorinated dibenzo- p -dioxin and dibenzofuran and dioxin-like polychlorinated biphenyl TEQs found in fish from the Bohai in previous studies, and made marginal contributions to overall human exposure to dioxin-like TEQs, suggesting that PCNs pose no toxicological concerns. Graphical abstract: Highlights: Homolog profiles indicated industrial thermal processes are the main PCN sources. Trophic magnification potentials for all PCN homologs were determined. TMF > 1 for di-CNs and tri-CNs was determined for the first time. Abstract : Trophic magnification potentials for all polychlorinated naphthalene homologs, including the rarely previously quantified dichloronaphthalenes, were determined in fish.